2018
DOI: 10.3847/1538-4357/aad908
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Homogeneity of Sun-like Stars in the Solar Neighborhood

Abstract: The compositions of stars are a critical diagnostic tool for many topics in astronomy such as the evolution of our Galaxy, the formation of planets, and the uniqueness of the Sun. Previous spectroscopic measurements indicate a large intrinsic variation in the elemental abundance patterns of stars with similar overall metal content. However, systematic errors arising from inaccuracies in stellar models are known to be a limiting factor in such studies, and thus it is uncertain to what extent the observed divers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

43
323
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 187 publications
(372 citation statements)
references
References 77 publications
43
323
6
Order By: Relevance
“…Moreover, local substructure of the plot for the elements Ca-Zn and neutron-addition elements is similar to that which can be found for solar twins. Our PDA versus Z plot structural shows similarity to plots that can be made from the extensive work of Bedell et al (2018). That PDA structure and substructure is clearly a function of age.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Moreover, local substructure of the plot for the elements Ca-Zn and neutron-addition elements is similar to that which can be found for solar twins. Our PDA versus Z plot structural shows similarity to plots that can be made from the extensive work of Bedell et al (2018). That PDA structure and substructure is clearly a function of age.…”
supporting
confidence: 63%
“…A primary advantage of the historical work, near independence from gf ‐values, is retained. The stars are chosen to have identical or nearly identical spectral types, and presumably closely comparable structures and abundances–to be “twins.” The precision of the method has revealed significant differences which may arise as a result of star formation and Galactic chemical evolution (GCE) (Bedell et al , henceforth BD18).…”
Section: Introductionmentioning
confidence: 99%
“…They found that 100 % of their sample of stars with detected planets has C/O< 0.8. Meanwhile, in a spectroscopic study of Sun-like stars, Bedell et al (2018) found that the ratios of C/O in solar metallicity stars are homogeneous to within 10 % throughout the solar neighborhood, implying that exoplanets may exhibit much less diversity in their composition than previously thought. The recent work by Pavlenko et al (2019) determined carbon and oxygen abundances in atmospheres of the supersolar metallicity stars with and without detected planets and confirmed that metal-rich dwarf stars with planets are more carbon-rich in comparison with nonplanet host stars, with a statistical significance of 96 %.…”
Section: Introductionmentioning
confidence: 94%
“…The past decade induced the theoretical and observational studies of carbon and oxygen abundances in stars in the context of determining a composition of extrasolar terrestrial planets, assuming that the composition of the host star and its protoplanetary disk is interrelated (see, e.g., Bond et al 2010;Petigura & Marcy 2011;Nissen et al 2014;Delgado Mena et al 2015;Madhusudhan et al 2016;Bedell et al 2018, and references therein). C and O and their elemental number rations C/O 1 could also be used to derive information related to the starplanet connection as in the case of lithium depletion.…”
Section: Introductionmentioning
confidence: 99%
“…Twin stars are objects with atmospheric parameters very similar to each other (e.g., ∆T eff 300 K and ∆log g 0.2 dex). It has been shown that a strictly differential line-by-line analysis of twin stars permits us to obtain differential abundances at the highest precision possible (e.g., Meléndez et al 2009;Bedell et al 2014Bedell et al , 2018Liu et al 2014;Spina et al 2018). In fact, when studying samples of twin stars, most of the systematic uncertainties that plague chemical abundance analyses are so similar among stars in the same binary pair that a strict differential line-by-line analysis cancels them out.…”
Section: Observations and Analysismentioning
confidence: 99%